Micrometer‐resolution imaging using MÖNCH: towards G2‐less grating interferometry. (17th October 2016) - Cartier, Sebastian; Kagias, Matias; Bergamaschi, Anna; Wang, Zhentian; Dinapoli, Roberto; Mozzanica, Aldo; Ramilli, Marco; Schmitt, Bernd; Brückner, Martin; Fröjdh, Erik; Greiffenberg, Dominic; Mayilyan, Davit; et al.
Abstract : The MÖNCH 25 µm‐pitch hybrid pixel detector is described in detail and characterized. The interpolation algorithm developed to achieve micrometer‐level resolution is applied to grating interferometry measurements. Abstract : MÖNCH is a 25 µm‐pitch charge‐integrating detector aimed at exploring the limits of current hybrid silicon detector technology. The small pixel size makes it ideal for high‐resolution imaging. With an electronic noise of about 110 eV r.m.s., it opens new perspectives for many synchrotron applications where currently the detector is the limiting factor, e.g. inelastic X‐ray scattering, Laue diffraction and soft X‐ray or high‐resolution color imaging. Due to the small pixel pitch, the charge cloud generated by absorbed X‐rays is shared between neighboring pixels for most of the photons. Therefore, at low photon fluxes, interpolation algorithms can be applied to determine the absorption position of each photon with a resolution of the order of 1 µm. In this work, the characterization results of one of the MÖNCH prototypes are presented under low‐flux conditions. A custom interpolation algorithm is described and applied to the data to obtain high‐resolution images. Images obtained in grating interferometry experiments without the use of the absorption grating G2 are shown and discussed. Perspectives for the future developments of the MÖNCH detector are also presented.